Matching in the Kolm Triangle: Interiority and Participation Constraints of Matching Equilibria - Wolfgang Buchholz; Richard Cornes; Dirk Rübbelke (Fondazione Eni Enrico Mattei (FEEM), 2019)
In this paper we show how the Kolm triangle method, which is a standard tool for visualizing allocations in a public good economy, can also be used to provide a diagrammatical exposition of matching mechanisms and their effects on public good supply and welfare. In particular, we describe, on the one hand, for which income distributions interior matching equilibria result and, on the other hand, for which income distributions the agents voluntarily participate in a matching mechanism. As a novel result, we especially show that the “participation zone” is larger than the “interiority zone”.
Keywords: C78; H41; 330; Public Goods; Matching; Pareto Optimality; Kolm Triangle; Aggregative Games